Midterm Outcomes, Complications, and Return to Sports After Medial Collateral Ligament and Posterior Oblique Ligament Reconstruction for Medial Knee Instability: A Systematic Review. Issue 11 (29th November 2021) - D'Ambrosi, Riccardo; Corona, Katia; Guerra, Germano; Cerciello, Simone; Ursino, Nicola; Cavaignac, Etienne; Vieira, Thais D.; Sonnery-Cottet, Bertrand
Background: In cases of multiple ligaments or medial collateral ligament (MCL) reconstruction, restoring the native anatomy of the posterior oblique ligament (POL) to address chronic valgus instability has been attracting increased attention. Purpose: To review the current literature on postoperative outcomes, complications, and return to sports after superficial MCL-POL (sMCL-POL) reconstruction to restore medial knee integrity. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review was conducted based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Two independent reviewers searched the PubMed, Scopus, Embase, and Cochrane Library databases using the terms "posterior oblique ligament, " "posteromedial corner of the knee, " and "reconstruction." Included were studies that reported postoperative clinical and functional outcomes in patients who had undergone a combined sMCL-POL reconstruction for medial knee instability. The authors evaluated surgical technique, rehabilitation protocol, postoperative outcomes (Lysholm, International Knee Documentation Committee [IKDC], and Tegner scores and valgus stress radiograph), and return to sports and complication rates across the included studies. Results: A total of 6 studies were reviewed. The cohort consisted of 199 patients (121 men and 78 women), with a mean age of 32.7 ± 3.9 years (range, 27.4-36.6 years). The Lysholm and IKDC scores improved from pre- to postoperatively (Lysholm, from 67.2 ± 20.4 to 89.4 ± 3; IKDC, from 45.8 ± 2.1 to 84.8 ± 7.5). The Tegner score produced satisfactory results, from a preoperative mean of 3.3 ± 2.4 to 6.3 ± 0.9 postoperatively. The medial joint opening on valgus stress radiographs ranged from 7.5 ± 1.1 mm preoperatively to 3 ± 3.1 mm postoperatively. After passing activity-specific functional and clinical tests, 88% to 91.3% of the patients were reported to have returned to recreational sports within 6 to 12 months postoperatively, whereas 10% of the patients developed postoperative complications. Conclusion: Satisfactory clinical and functional outcomes, a high rate of return to recreational sports, and a low rate of postoperative complications were reported after an sMCL-POL reconstruction to restore medial knee integrity.